The genomic basis of childhood T-lineage acute lymphoblastic leukaemia - Pölönen, Petri; Di Giacomo, Danika; Seffernick, Anna Eames; Elsayed, Abdelrahman; Kimura, Shunsuke; Benini, Francesca; Montefiori, Lindsey E.; Wood, Brent L.; Xu, Jason; Chen, Changya; Cheng, Zhongshan; Newman, Haley; et al. (Nature (London), 2024)
T-lineage acute lymphoblastic leukaemia (T-ALL) is a high-risk tumour 1 that has eluded comprehensive genomic characterization, which is partly due to the high frequency of noncoding genomic alterations that result in oncogene deregulation 2 , 3 . Here we report an integrated analysis of genome and transcriptome sequencing of tumour and remission samples from more than 1,300 uniformly treated children with T-ALL, coupled with epigenomic and single-cell analyses of malignant and normal T cell precursors. This approach identified 15 subtypes with distinct genomic drivers, gene expression patterns, developmental states and outcomes. Analyses of chromatin topology revealed multiple mechanisms of enhancer deregulation that involve enhancers and genes in a subtype-specific manner, thereby demonstrating widespread involvement of the noncoding genome. We show that the immunophenotypically described, high-risk entity of early T cell precursor ALL is superseded by a broader category of ‘early T cell precursor-like’ leukaemia. This category has a variable immunophenotype and diverse genomic alterations of a core set of genes that encode regulators of hematopoietic stem cell development. Using multivariable outcome models, we show that genetic subtypes, driver and concomitant genetic alterations independently predict treatment failure and survival. These findings provide a roadmap for the classification, risk stratification and mechanistic understanding of this disease. Comprehensive genomic and transcriptomics analyses of more than 1,300 cases of childhood T-lineage acute lymphoblastic leukaemia identify 15 distinct subtypes that are associated with specific outcomes.